VD_FINDINFO Jug / 2025 / 138 vom 16. Mai 2024 - VD Tribunal cantonal (2024)
CALOMNIE, DIFFAMATION, CONTRAINTEDROIT PÉNAL, TENTATIVEDROIT PÉNAL, REJET DE LA DEMANDE, ACQUITTEMENT | 173 ch. 1 CP, 174 ch. 1 CP, 181 CP, 22 ad 181 CP